Analisis Serangan Mongol Pada Wilayah Muslim - Arfah, Andi Muhammad Awaluddin; Firmansyah, Fiqih; Sulaiman, Umar (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Islam will not be destroyed by physical destruction. The devastating blow of the Mongol troops that killed millions of Muslims actually raised the spirit of Muslims to unite. The land of Syria, which was previously hostile to Egypt, finally united against the Mongol troops and forgot their hostility. With unity, they won the war of 'Ain Jalut. This study is a historical study to see the incident of the Mongol attack on Muslim territory. In this study, the researcher used a qualitative descriptive approach with a data collection method from library data. As is common in historical studies, the best data is data that is closest in tempo to the event being discussed. This study begins with data coding, data reduction and drawing conclusions as is commonly used in qualitative analysis. The results of the study show that the defeat of the Muslims against the Mongols was not only because the Mongol troops were trained in war, but also due to the internal weaknesses of the Muslims. Muslim countries were divided and many of their rulers and people lived in worldly luxury which caused them to be unprepared to carry out jihad.